Work Motivation Mediates Organizational Culture on Performance - Natalia, Lisa (Journal of Business Management and Economic Development, 2023)
The purpose of this study is to examine the variables of Organizational Culture and Competence that can have an impact on Employee Performance through the Motivation of the Library and Archives Office of East Java Province. Researchers here apply quantitative research and descriptive methods as research methods, and data collection techniques using observation, interviews, and questionnaires which are disseminated to respondents via the Google form. The population of this study uses the East Java Library and Archive Service Employees. The research sample used non-probability sampling from a purposive sampling approach of 54 employees. This study analyzes using PLS. The results of the study prove that Organizational Culture influences employee performance, Competence does not affect Employee Performance, Culture has an impact on Motivation, Competence has an impact on Motivation, Motivation has an impact on Employee Performance, Motivation can mediate Organizational Culture on Employee Performance, and Motivation cannot mediate Competency on Employee Performance at the Library and Archives Service of East Java Province.